Lactocollybia aurantiaca Singer (Tricholomataceae, Basidiomycota): first record from Brazil - Putzke, Jair (SITIENTIBUS série Ciências Biológicas, 2007)
This work is part of the taxonomic study of the Tricholomataceae (Agaricales, Basidiomycota) found in the state of Rio Grande do Sul, Brazil. Lactocollybia aurantiaca Singer is recorded for the first time from Brazil based on a collection done in Rio Grande do Sul. Descriptions and illustrations of this species are presented.